2021
DOI: 10.1017/cjn.2021.214
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Cervical Myelopathy: Towards a Personalized Approach

Abstract: Degenerative cervical myelopathy (DCM) is a recently coined term encompassing a variety of age-related and genetically associated pathologies, including cervical spondylotic myelopathy, degenerative disc disease, and ligamentous aberrations such as ossification of the posterior longitudinal ligament. All of these pathologies produce chronic compression of the spinal cord causing a clinical syndrome characterized by decreased hand dexterity, gait imbalance, and potential genitourinary or sensorimotor disturbanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 104 publications
0
19
0
Order By: Relevance
“…With a personalized approach, treatment outcomes can be enhanced in all the cases. The operative approach, pre-and post-operative care can be personalized and optimized for achieving favorable patient outcomes [65]. An extensive population of a country like ours will need care at decreased costs, which would thus affect the innovation in our specialty.…”
Section: Discussionmentioning
confidence: 99%
“…With a personalized approach, treatment outcomes can be enhanced in all the cases. The operative approach, pre-and post-operative care can be personalized and optimized for achieving favorable patient outcomes [65]. An extensive population of a country like ours will need care at decreased costs, which would thus affect the innovation in our specialty.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with DCM present a broad spectrum of symptoms, ranging from subtle sensory neuropathic symptoms to motor weakness with functional disability, depending on disease progression and severity ( 2 ). Patients with DCM require early diagnosis and management; specifically, it is essential to determine an appropriate therapeutic option according to the disease severity while minimizing damage to the spinal cord ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comorbidities in this population require personalized approaches considering frailty. 5,6 Studies have shown that frailty, particularly measured by mFI-5, is more predictive than age in patients with DCM in predicting adverse events, hospital stay, and discharge. 7 Although various frailty measures exist, mFI-5 and mFI-11 are the most suitable, offering generalizability, objectivity, and high reproducibility.…”
mentioning
confidence: 99%